TDP2 drives immune evasion and metastatic progression in prostate cancer - Huan Cao; Anyin Pan; Yuetao Chen; Fei Zheng (PLoS ONE, 2026)
Immune evasion and epithelial-mesenchymal transition (EMT) are critical mechanisms driving tumor progression and therapy resistance in prostate cancer. In this study, we explored the role of TDP2 in modulating the tumor microenvironment (TME) through single-cell RNA sequencing and pathway enrichment analysis. Our results revealed that epithelial cells with high TDP2 expression extensively interact with myeloid cells, macrophages, and fibroblasts, thereby shaping immune responses and facilitating tumor progression. Specifically, TDP2 overexpression suppressed M1 macrophage polarization and dendritic cell (DC) maturation, leading to reduced CD8 + T cell activation and enhanced immune evasion. Additionally, TDP2-high expression was associated with enriched signaling pathways involved in EMT, including COLLAGEN, GALECTIN, MIDKINE (MK), and ONCOSTATIN M (OSM), which promoted tumor cell migration, invasion, and immune evasion. Survival analyses further demonstrated that high TDP2 expression correlated with poor clinical outcomes in prostate cancer patients. Overall, our findings identify TDP2 as a key regulator within the TME and suggest its potential utility as both a prognostic biomarker and therapeutic target in prostate cancer.